Pressure capacity of sandwich pipe with cement-based core configuration under deep-water external pressure. (May 2020) - Wan, Feng; Guan, Feng; Zhou, Chuanxi; Liu, Shaohu; Yang, Ting
Sandwich pipe, consisting of two steel tubes and a polymeric or cement-based material core layer, has been considered as an attractive solution for oil and gas transporting in deep water. In this paper, the characteristic responses and pressure capacity of sandwich pipes having fiber-reinforced cementitious composites core configuration under external hydrostatic pressure were investigated. The interface adhesion behavior between the fiber-reinforced cementitious composite core and the surrounding steel pipes was modeled based on the inter-layer shear strength test experiments conducted on the sandwich pipe specimens. The parametric studies were carried out to evaluate the influence of geometry parameters and steel grade on the buckling response and ultimate pressure capacity. Furthermore, 768 FE models of sandwich pipes covering a wide range of practical design configurations were rapidly constructed and analyzed using FE software package ABAQUS with the help of programming language Python. Finally, a simplified equation for predicting the pressure capacity of sandwich pipes within the scope of this study was proposed using dimensional analysis combined with singular value decomposition methodology.